THE USE OF POWTOON AS LEARNING MEDIA TO REDUCE TEACHER’S ANXIETY IN TEACHING CLASSROOM - Sersanawawi, Lisa; Daulay, Sholihatul Hamidah; Rahmah, Isnayni (Universitas PGRI Sumatera Barat, 2024)
Improving the quality of teaching requires a thorough attention on various critical areas. Anxiety is a significant issue in the classroom, which has an impact on the current subject being discussed. Novice educators often encounter nervousness. Teaching loses its effectiveness in terms of conveying information to pupils. The presence of anxiety throughout the learning process has negative effects on the level of discomfort experienced. Technological advancements can significantly reduce this problem, especially in reducing anxiety throughout the learning process. This study aimed to assess the effectiveness of using the PowToon application in reducing teacher anxiety while teaching English as a Foreign Language (EFL) courses. This literature study analyzed eight scholarly studies that investigated the effects of incorporating PowToon and other electronic media in educational training. The study's findings indicate that PowToon provides a multitude of advantages for learning. PowToon is highly regarded as a helpful tool for educators due to its ability to facilitate teaching and explanation. Using PowToon helps stimulate students' creativity by mitigating the monotony sometimes associated with uninteresting educational settings. The findings suggest that the use of PowToon media can successfully reduce anxiety, boost instructor confidence, and make the learning process more enjoyable. Hence, this study can provide valuable perspectives for instructors who lack confidence in their pedagogical skills.